La Enseñanza del Inglés y la Empresa Privada en Colombia: Una Perspectiva Empresarial y un Desafío para los Educadores (GIST – Education and Learning Research Journal, 2007)
Teaching English to employees, and maintaining the language levelsof those already hired, is a constant and growing concern for thoseresponsible for corporate education in Colombia’s private sector.Although it might be argued that acquisition and maintenance of asecond language is an individual responsibility, when faced with anincreasingly globalized economy and the resultant use of English asthe language of business, private enterprise in Colombia has had tointervene in a systemic problem resulting from deficiencies in private and public secondary and higher education, as well as in private language institutes.